2003
DOI: 10.1191/0960327103ht394oa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of historical control data in carcinogenicity studies

Abstract: Results obtained in long-term carcinogenicity studies with animals should be evaluated, first and foremost, by statistical comparisons of the data obtained from the treated group with that from the concurrent control group. Often the results are compared with data from so-called historical control groups in order to take variations in the incidences of spontaneous tumours into account. Because historical control data change in the course of time and for a variety of reasons, certain requirements must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…It has been highlighted that historical control data has a role in the evaluation of rare neoplasms, high-incidence tumors, marginal increases in incidence and in the assessment of the quality of a study (Greim et al, 2003). However, it is known that variation of incidence of tumor types within the same strain and sex and, within the same laboratory, occur due to the progression of time (Gopinath, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…It has been highlighted that historical control data has a role in the evaluation of rare neoplasms, high-incidence tumors, marginal increases in incidence and in the assessment of the quality of a study (Greim et al, 2003). However, it is known that variation of incidence of tumor types within the same strain and sex and, within the same laboratory, occur due to the progression of time (Gopinath, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The need for a formal method of incorporating historical control data in the analysis of the current experiment has long been recognized (Haseman et al, 1984;Haseman 1995), but no procedure has emerged as the clear favorite (Greim et al, 2003). The Technical Reports Review Subcommittee of the NTP Board of Scientific Counselors, which includes two statisticians, has not endorsed any of the current methods and recommended a new procedure be developed for this important problem (http://ntp.niehs.nih.gov/files/TRRSMins0905.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous incidences and use of historical control data(Dinse and Peddada 2011; Greim et al 2003; Keenan et al 2008; Ma et al 2002; Massarelli et al 2013)Relevance for humans, e.g. species-specific mechanism that does not operate in humansThe use of historical data is mentionedAll valid studies are considered negative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to best practices (Greim et al 2003; Keenan et al 2009), graphical visualisations (Elmore and Peddada 2009) and statistical approaches (Dinse and Peddada 2011; Peddada et al 2007) have been developed, although direct comparison with the historical control range in the test laboratory around the time of the study is the approach mostly used in the regulatory context, and preferred in the EU assessment. This approach was considered for malignant lymphomas and haemangiosarcomas in mice when the studies reported the historical range for the test laboratory.…”
Section: Discussionmentioning
confidence: 99%